Percutaneous coronary intervention during index admission versus pharmacoinvasive strategy for treatment of patients with acute st-elevation myocardial infarction in Hospital USM ; a 5 years experience - Mohammed, Muaath Ahmed Hasan (2021)
The pharmaco-invasive strategy is one of the standards of care in patients with ST-elevation myocardial infarction (STEMI), but the optimal timing may not be achieved due to limitations. Thus a large number of patients underwent percutaneous coronary intervention (PCI) at a later timing during their index hospitalisation. However, little evidence is available on the outcome of this strategy. This study aimed to compare the clinical outcomes of PCI during index admission with a pharmaco-invasive strategy for patients with STEMI. This retrospective cohort study was conducted at Hospital Universiti Sains Malaysia (HUSM). Medical records of all STEMI patients who were treated by PCI from January 2013 to March 2018 were retrieved. The clinical outcomes of the study were the rate of Major Adverse Cardiac Event (MACE) and major bleeding at 30 days and six months post PCI. The multiple logistic regression analysis was used to determine the associated factors with MACE outcome. A total of 91 STEMI patients were analysed. Twenty-nine (21.9%) patients were treated by pharmaco-invasive strategy, and 62 (68.1%) patients underwent PCI during their index admission. At 30 days post PCI, the rate of MACE in the pharmaco-invasive and PCI during index admission groups were 10.7% vs 10.3% respectively (p = 0.958). The rates at six months were 8.3% vs.7.8% respectively (p = 0.94). The rates of major bleeding at 30 days was one (3.6%) and none (p = 0.151) . By contrast, the rate at six months was seen only in one (2.0%) for the PCI during index admission group. The results of MLogR analysis showed that the variables of gender (odds ratio [OR]: 10.9, 95% confidence interval [CI]:1.35-87.80, p = 0.025), Heart rate (OR: 1.095, 95% CI: 1.031-1.164, p =0.003), and systolic BP (OR: 0.92, 95% CI: 0.87-0.97, p = 0.005) were a significant factors associated with MACE outcome at 30 days post PCI. At six months, the history of previous CAD (OR: 27.41, 95% CI: (1.97-380.21, p = 0.014), heart rate (OR: 1.04, 95% CI: 1.02-1.14, p = 0.003), and systolic BP (OR: 0.93, 95% CI: 0.88- 0,98, p = 0.017) were significantly associated with MACE. This study suggests that PCI during index admission may had similar clinical outcomes to a pharmaco-invasive strategy.